Krakatau on Fire, The Disaster of 1883 in Dutch Colonial Literature: A Postcolonial Approach - Honings, Rick (UI Scholars Hub, 2020)
In 1883, the volcano Krakatau erupted and collapsed, causing the deaths of tens of thousands. The eruption was one of the first disasters to take place beyond the Dutch boundaries that received so much attention in the Netherlands. Although the disaster appealed to the imagination, it barely led to the publication of fiction. Only in Dutch Indies youth literature can one find something about the Krakatau. In this article, four Dutch stories and novels are analysed: “Stories of the moon” by Nellie van Kol-Porreij, The hermit of Rakata or Krakatau on fire by Robert Michael Ballantyne, “Nine Months on Krakatau” by B.L. Kailola and Escaped from the jaws of death: The Krakatau tragedy by Rick Blekkink. These sources are analysed from a postcolonial perspective, focusing on unequal power relations. Focal points are the representation of the Indies and the indigenous people of the colony. This article illustrates the continuities and shifts in the representations over de course of time (1886–2014).